Comparison of T2, T1rho, and diffusion metrics in assessment of liver fibrosis in rats. Issue 3 (16th August 2016) - Zhang, Hui; Yang, Qihua; Yu, Taihui; Chen, Xiaodong; Huang, Jingwen; Tan, Cui; Liang, Biling; Guo, Hua
Abstract : Purpose: To evaluate the value of T 2, T 1 rho, and diffusion metrics in assessment of liver fibrosis in rats. Materials and Methods: Liver fibrosis in a rat model ( n  = 72) was induced by injection of carbon tetrachloride (CCl4 ) at 3T. T 2, T 1 rho, and diffusion parameters (apparent diffusion coefficient (ADC), Dtrue ) via spin echo (SE) diffusion‐weighted imaging (DWI) and stimulated echo acquisition mode (STEAM) DWI with three diffusion times (DT: 80, 106, 186 msec) were obtained in surviving rats with hepatic fibrosis ( n  = 52) and controls ( n  = 8). Liver fibrosis stage (F0–F6) was identified based on pathological results using the traditional liver fibrosis staging method for rodents. Nonparametric statistical methods and receiver operating characteristic (ROC) curve analysis were employed to determine the diagnostic accuracy. Results: Mean T 2, T 1 rho, ADC, and Dtrue with DT = 186 msec correlated with the severity of fibrosis with r  = 0.73, 0.83, −0.83, and −0.85 (all P < 0.001), respectively. The average areas under the ROC curve at different stages for T 1 rho and diffusion parameters (DT = 186 msec) were larger than those of T 2 and SE DWI (0.92, 0.92, and 0.92 vs. 0.86, 0.82, and 0.83). The corresponding average sensitivity and specificity for T 1 rho and diffusion parameters with a long DT were larger (89.35 and 88.90, 88.36 and 89.97, 90.16 and 87.13) than T 2 and SE DWI (90.28 and 79.93, 85.30 and 77.64, 78.21 and 82.41). The performances of T 1 rho and Dtrue (DT = 186 msec) were comparable (average AUC: 0.92 and 0.92). Conclusion: Among the evaluated sequences, T 1 rho and STEAM DWI with a long DT may serve as superior imaging biomarkers for assessing liver fibrosis and monitoring disease severity. Level of Evidence: 1 J. Magn. Reson. Imaging 2017;45:741–750.